2020
DOI: 10.3390/tropicalmed5020074
|View full text |Cite
|
Sign up to set email alerts
|

New Imaging Parameters to Predict Sudden Cardiac Death in Chagas Disease

Abstract: Chronic Chagas’ cardiomyopathy is the most severe and frequent manifestation of Chagas disease, and has a high social and economic burden. New imaging modalities, such as strain echocardiography, nuclear medicine, computed tomography and cardiac magnetic resonance imaging, may detect the presence of myocardial fibrosis, inflammation or sympathetic denervation, three conditions associated with risk of sudden death, providing additional diagnostic and/or prognostic information. Unfortunately, despite its high mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…In the early stages (B1 or B2), the echocardiogram may demonstrate alterations of LV segmental mobility ranging from hypokinesia to aneurysm formation [2,121,122]. The cardiac regions frequently affected are the basal segments of the inferior and inferolateral wall and the apex, alterations that cannot be attributed to obstructive coronary artery disease.…”
Section: Echocardiogrammentioning
confidence: 99%
See 1 more Smart Citation
“…In the early stages (B1 or B2), the echocardiogram may demonstrate alterations of LV segmental mobility ranging from hypokinesia to aneurysm formation [2,121,122]. The cardiac regions frequently affected are the basal segments of the inferior and inferolateral wall and the apex, alterations that cannot be attributed to obstructive coronary artery disease.…”
Section: Echocardiogrammentioning
confidence: 99%
“…The study of segmental mobility alterations is subjective, so the evaluation of deformation by two-dimensional speckle tracking (2DST) can become a useful tool in the early stages by identifying alterations in areas without apparent involvement [5,123]. The use of 2DST is less useful in patients with obvious segmental mobility disorders (Figure 6), but it still serves as a tool to assess the heterogeneity of systolic contraction (mechanical dispersion); these alterations are associated with ventricular arrhythmias independent of LVEF [122,124].…”
Section: Echocardiogrammentioning
confidence: 99%
“…In this scenario, 18 F-FDG PET may be a promising tool to monitor disease activity and risk stratification of patients with CC. Future studies should address these new potential clinical applications of PET imaging 73,74 (Figure 6).…”
Section: Chagas Cardiomyopathymentioning
confidence: 99%
“…27 The close relationship of MF, ventricular arrhythmias, and sudden cardiac death has been described by several studies on ischemic and nonischemic cardiomyopathies. [28][29][30][31][32] Distinguishing different patterns of MF and determining its extent by LGE-CMR provides important information that allows physicians to distinguish the etiology of cardiomyopathies and improve prognosis scores. White et al, 33 demonstrated that the etiology of aborted sudden cardiac death or sustained monomorphic ventricular tachycardia was changed in 50% of the cases where patients were evaluated by CMR in comparison to conventional diagnostic investigation with transthoracic echocardiography and coronary angiography.…”
Section: Cmr As a Risk Stratification Toolmentioning
confidence: 99%